Potential of low-cost TiO2-PVC composite in photoelectrocatalytic degradation of reactive orange 16 under visible light - Lahuri, Azizul Hakim (Springer Berlin Heidelberg, 2023)
In recent years, previously reported studies revealed a high efficiency of pollutant degradation by coupling photocatalysis and electrochemical processes (PECs) using titanium dioxide (TiO2) photoelectrode rather than using photocatalysis or electrocatalysis alone. However, some of the TiO2 photoelectrodes that have been reported were not cost-effective. This is due to the use of expensive chemicals and certain expensive equipment in the fabrication process, other than involving complicated preparation steps. Therefore, this study is aimed at investigating the PEC performance and stability of low-cost TiO2-polyvinyl chloride (TiO2-PVC) composite photoelectrode for Reactive Orange 16 (RO16) degradation. The materials characterisation using the ATR-FTIR, XRD and UV-Vis DRS proved that TiO2 and TiO2-PVC were successfully synthesised. The micrograph obtained for the surface characterisation using the FESEM showed that the smooth surface of freshly prepared photoelectrodes turned slightly rough with tiny pits formation after five continuous PEC processes. Nevertheless, the photoelectrode retained its original shape in good condition for further PEC processes. By PEC process, the fabricated photoelectrode showed 99.4% and 51.1% of colour and total organic carbon (TOC) removal, respectively, at optimised PEC parameters (1.0 mol L−1 NaCl concentration, 10 V applied voltage, 120 min degradation time and initial pH 2). Moreover, the fabricated photoelectrode demonstrated sufficient reusability potential (~ 96.3%) after five cycles of PEC processes. In summary, a low-cost and stable composite photoelectrode with high efficiency in RO16 degradation was successfully fabricated and could be potentially applied for other emerging pollutants degradation via the PEC degradation technique.